Uma Solução para crowdfunding com transparência em investimentos baseada em blockchain - Maia, Delano José Holanda (2022)
The emergence of startups has been increasingly common on the world stage. Many good ideas end up emerging in the midst of scenarios that we go through on a daily basis. In most cases, the person or group who determined and idealized an idea for a product or service, do not put the project ahead due to lack of money for, for example, initial costs with prototyping. With this, promising ideas end up being forgotten and lost over time. Sites where several people find a project coming out of the paper are easily found on the internet, called crowdfunding. In them we can find game projects, innovative or even common products, but with a new approach, either with greater ease of use or with reduced costs. Through these sites we have many forms of payment, credit card, bank slip, PIX, bank transfers or cryptocurrencies. The blockchain stands out with applications in cryptocurrencies, using smart contracts, it adds credibility as transactions carried out, even if in a decentralized way. Smart contracts began to be used due to the addition of customization offered to transactions, paving the way in the search for blockchain solutions to problems encountered in society. The objective of this work is to propose an architecture and solution to the problem of traceability of the money invested by project financers, offering a little more control over the investment, a decision-making power when the project manager starts to spent the money raised. Finally, we have an analysis of financial costs and transaction times on the Ethereum network, helping investors to understand where the funds raised are going.